The World of Languages and Literatures A Contemporary Outlook. - Bakić-Mirić, Natasa (Cambridge Scholars Publisher, 2021)
This book offers contemporary perspectives on different registers of instruction, media language, the effectiveness of a multi-literacies program for introducing English as a Foreign Language, promoting religious tolerance through literature and music, teaching drama, intercultural communication, gender studies and literature studies. By using contemporary research methods, the contributors here offer insights into the ways in which the world of languages and literatures changes and evolves to face the constant challenges resulting from new instructional practices and research investigations,